The Impact of Gabapentin Administration on Brain GABA and Glutamate Concentrations: A 7T 1H-MRS Study - Cai, Kejia; Nanga, Ravi PR; Lamprou, Lisa; Schinstine, Claudia; Elliott, Mark; Hariharan, Hari; Reddy, Ravinder; Epperson, C Neill (Neuropsychopharmacology (New York, N.Y.), 2012)
Gamma-aminobutyric acid (GABA) and glutamate are implicated in numerous neuropsychiatric and substance abuse conditions, but their spectral overlap with other resonances makes them a challenge to quantify in humans. Gabapentin, marketed for the treatment of seizures and neuropathic pain, has been shown to increase in vivo GABA concentration in the brain of both rodents and humans. Gabapentin effects on glutamate are not known. We conducted a gabapentin (900 mg) challenge in healthy human subjects to confirm and explore its effects on GABA and glutamate concentrations, respectively, and to test the ability of single voxel localized proton magnetic resonance spectroscopy (¹H-MRS) to reliably measure GABA and glutamate in the visual cortex at the ultra-high magnetic field of 7 Tesla. Reproducibility of GABA and glutamate measurements was determined in a comparison group without drug twice within day and 2 weeks apart. Although GABA concentration changes were small both within day (average 5.6%) and between day (average 4.8%), gabapentin administration was associated with an average increase in GABA concentration of 55.7% (6.9-91.0%). Importantly, drug-induced change in GABA levels was inversely correlated to the individual's baseline GABA level (R²=0.72). Mean glutamate concentrations did not change significantly with or without drug administration. In conclusion, localized ¹H-MRS at 7 Tesla can be successfully applied to the measurement of GABA concentration and is sensitive to acute drug-induced changes in cortical GABA. Whether baseline GABA concentrations predict clinical efficacy of gabapentin is an area worthy of exploration.